Status of the antennas at the IceCube Surface Array Enhancement - Venugopal, Megha; IceCube Collaboration (2025)
IceCube is a cubic km detector at the South Pole comprising two main components, the neutrino detector that measures neutrinos in-ice, the IceCube Neutrino Observatory and IceTop, a surface cosmic-ray detector constituting 81 pairs of ice-filled Cherenkov tanks. An extension with multiple stations, each station equipped with 8 elevated scintillators and 3 antennas, was planned on the IceTop footprint to complement existing measurement methods and to serve as part of a larger surface array for IceCube-Gen2. In early 2023, the scintillators of the single deployed station of the IceCube Surface Enhancement were upgraded, increasing the dynamic range and enabling the reconstruction of more coincident air showers. An updated dataset combining data from radio and IceTop detectors is presented. Additionally, the current status of the deployment of new stations is discussed.